Analisis Profil Gaya Belajar Peserta Didik Sebagai Data Pembelajaran Berdiferensiasi di kelas VII SMP Negeri 01 Jaya Pura - Evi Susanti; Ismet; Ketang Wiyono (Jurnal Penelitian Pendidikan IPA, 2023)
This research aims to analyze the learning styles of grade 7 students at SMP Negeri 01 Jaya Pura for the 2023-2024 academic year in East Oku Regency, South Sumatra Province. This research is a qualitative descriptive study. The subjects of this research were all 7th grade students of SMP Negeri 01 Jaya Pura for the 2023-2024 academic year in East Oku Regency, South Sumatra Province. The data collection technique used in this research is in the form of a questionnaire which will be filled out by research subjects. Then the data will be analyzed quantitatively by calculating the percentage that refers to the three VAK learning styles (Visual, Auditory and Kinesthetic). The results of the learning style analysis of all 7th grade students at SMP Negeri 01 Jaya Pura for the 2023-2024 academic year showed that there were 40% Visual learning styles, 23% Auditory learning styles, 31% Kinesthetic learning styles, 2% Visual Kinesthetic learning styles, 1% auditory visual learning is as much as 1% of the auditory kinesthetic learning style and 2% of the visual auditory kinesthetic learning style. From this research, it was concluded that the learning style of students in Class 7 of SMP Negeri 01 Jaya Pura for the 2023-2024 academic year was dominated by the visual learning style at 40% of the total class of students. These differences in student learning style tendencies can be accommodated by conducting differentiated learning so that it can meet student needs and student characteristics. Â